PROMOTING SPEAKING THROUGH GRAPHIC LITERATURE FOR EFL LEARNERS - Eva Solina Gultom (UICELL, 2021)
This research probes the effectiveness of literature used in improving speaking skills for EFL learners. The specific literature that applied for this learning is graphic literature. As part of literature, graphic literature has become one of the resources that provide aesthetic, creativity, intellectuality, and imaginative experience of writers for learners. This research used the quantitative method that focuses on data analysis through online class observation and surveys. The objectives of this research are to exhibit the ways of literature implied to teach speaking for EFL learners, to delineate the potency of graphic literature to escalate speaking skills for EFL learners, and to perceive students' discernments of studying literature through graphic literature in advancing speaking competence for EFL learners. Keywords: EFL learners, graphic literature, literature, speaking, teaching